(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Plastics are manufactured natural polymers that are broadly utilized in an assortment of utilizations, including water bottles, garments, food bundling, clinical supplies, innovative things, and building materials. Plastics have developed into an indispensable and versatile product with an expansive assortment of characteristics, synthetic organizations, and utilizations during the past sixty years. Plastic contamination is the development of manufactured plastic things in the climate to the point that they represent a danger to creatures and their natural surroundings, just as the human populace. Large number of industrial facilities are delivering huge loads of plastic sacks utilized prominently by individuals for the end goal of shopping as a result of their inexpensiveness, ease, just as accommodation of utilization. All things considered, their antagonistic impact is rarely featured or, in any event, straightforwardly talked about in a more genuine tone. The circumstance is deteriorated in Sierra Leone as a non-industrial nation. This paper talked about the antagonistic impacts of plastic contamination on the climate of Freetown and furthermore clarify the effect of plastic contamination. In the future carrying out standard guidelines for the creation and utilization of plastics will assist with diminishing the poisonous consequences for our current circumstance and wellbeing.